The Implementation of EFL Online Learning - de Fretes, Delila; Lekawael, Rosina F. J. (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study explores the effectiveness and broad adoption of online instruction for English as a Foreign Language (EFL). Considering the difficulties that instructors and students encounter in this kind of instruction, the study uses an extensive literature review approach. The goal is to underscore the positive impact of online learning on the sustainability of education and identify key factors that contribute to its effectiveness. Drawing literature from academic databases, journals, books, and reputable online platforms, the collection process is guided by specific terms like "EFL" and "Online Learning." Inclusion criteria target studies addressing the positive impacts and challenges of online learning in EFL. Thematic coding is applied to organize the literature into sections covering positive impacts, challenges, and influencing factors. Thematic analysis identifies common themes, while a comparative analysis emphasizes differences and similarities across studies, ensuring a cohesive exploration of the topic. The research suggests potential avenues for future studies to further enrich our understanding of online learning in the EFL context.